2022
DOI: 10.31025/2611-4135/2022.15217
|View full text |Cite
|
Sign up to set email alerts
|

Pulp and Paper Mill Sludge; a Soil Amendment and Compost option for Landfill Diversion for South-Africa

Abstract: In South-Africa, approximately 30% of all recycled paper is being disposed into landfill sites or incinerated. Using this type of hazardous and industrial waste as a resource is essential to reduce landfilling of organic waste. In this study, Pulp and Paper-Mill Sludge (PPMS) has been evaluated under two possible pathways contributing to landfill diversion and secondary use: compostability and the use of PPMS as a soil amendment. A short review of existing studies on PPMS using these two pathways as alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Based on these findings, it can be concluded that the mixture of toothache tree oilseed cake (TO) and peat moss (P), including PMS, was more effective in improving soil quality for plant growth when composted. Additionally, it can be inferred that PMS does not have any harmful effects on plant growth, even after composting [45]. Based on these findings, it can be concluded that the mixture of toothache tree oilseed cake (TO) and peat moss (P), including PMS, was more effective in improving soil quality for plant growth when composted.…”
Section: Seedling Tests In the Prepared Soil Modifiersmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on these findings, it can be concluded that the mixture of toothache tree oilseed cake (TO) and peat moss (P), including PMS, was more effective in improving soil quality for plant growth when composted. Additionally, it can be inferred that PMS does not have any harmful effects on plant growth, even after composting [45]. Based on these findings, it can be concluded that the mixture of toothache tree oilseed cake (TO) and peat moss (P), including PMS, was more effective in improving soil quality for plant growth when composted.…”
Section: Seedling Tests In the Prepared Soil Modifiersmentioning
confidence: 92%
“…In certain cases, a higher bulk density can actually benefit soil quality. For instance, it may aid in improving soil drainage and reducing erosion [44,45].…”
Section: Bulk Density Of Soil Modifiersmentioning
confidence: 99%
See 1 more Smart Citation